METODE PENAFSIRAN BUYA HAMKA DALAM TAFSIR AL-AZHAR - Alfiyah, Avif (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
Buya HAMKA, a prominent Indonesian Muslim leader, poet, author, historian, and educator, was so instrumental to Indonesian scientific development, especially for the world of Islam in Indonesia. The greatest work of him is his commentary entitled Tafsir al-Azhar. This article explains about the methodology of HAMKA?s interpretation on Qur?anic verses. In the conclusion, Tafsir al-Azhar can be classified as tafsîr bi al-ma?tsûr based on it source, with tahlîlî method because it is begun from Surah al-Fâtihah until Surah al-Nâs, muqârin method for its explanation, and categorized as tafsîr tafshîlî too according to his width exploration in the tafsir. While the feature of his tafsir is dominated by adâbî ijtimâ?î with the beauty of Malayan language related to the social reality in his era. After all, his tafsir is being easy to understand for Indonesian people as the majority reader of it.